2008
DOI: 10.1172/jci34588
|View full text |Cite
|
Sign up to set email alerts
|

Acquired resistance to EGFR tyrosine kinase inhibitors in cancer cells is mediated by loss of IGF-binding proteins

Abstract: Although some cancers are initially sensitive to EGFR tyrosine kinase inhibitors (TKIs), resistance invariably develops. We investigated mechanisms of acquired resistance to the EGFR TKI gefitinib by generating gefitinibresistant (GR) A431 squamous cancer cells. In GR cells, gefitinib reduced phosphorylation of EGFR, ErbB-3, and Erk but not Akt. These cells also showed hyperphosphorylation of the IGFI receptor (IGFIR) and constitutive association of IRS-1 with PI3K. Inhibition of IGFIR signaling disrupted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
379
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(403 citation statements)
references
References 49 publications
17
379
2
3
Order By: Relevance
“…Consistent with the concept that the IGFBP-3-dependent growth stimulation was mediated through EGFR, only the IGFBP-3-expressing cells were growth-inhibited in cell culture by an EGFR kinase inhibitor (Butt et al 2004). Interestingly, a more recent study using A431 epidermoid carcinoma cells similarly found that the development of resistance to the EGFR inhibitor gefitinib was associated with low IGFBP-3 expression, again supporting the idea that IGFBP-3 might be helping to drive cell growth through EGFR activation (Guix, et al 2008).…”
Section: Egfr Igf1r and Sphingosine Kinase Signalingmentioning
confidence: 86%
“…Consistent with the concept that the IGFBP-3-dependent growth stimulation was mediated through EGFR, only the IGFBP-3-expressing cells were growth-inhibited in cell culture by an EGFR kinase inhibitor (Butt et al 2004). Interestingly, a more recent study using A431 epidermoid carcinoma cells similarly found that the development of resistance to the EGFR inhibitor gefitinib was associated with low IGFBP-3 expression, again supporting the idea that IGFBP-3 might be helping to drive cell growth through EGFR activation (Guix, et al 2008).…”
Section: Egfr Igf1r and Sphingosine Kinase Signalingmentioning
confidence: 86%
“…Other acquired gefitinib-resistant cancer cells were established by selecting with gradually elevated concentrations of gefitinib for two months as described previously (16). Insensitivity to gefitinib treatment was tested in these established resistant cancer cell lines, which were cultured in the presence of 1 M gefitinib.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike the well characterized studies between EGFR mutation and gefitinib sensitivity (5)(6)(7)(8), a few studies have addressed the molecular determinants accounting for the cellular sensitivity to gefitinib in wtEGFR-expressing cancer cells. In a cell culture system with acquired resistance to gefitinib, an increased activity of insulin-like growth factor receptor by down-regulating insulin-like growth factor-binding proteins has been found to maintain the PI3K/Akt-mediated survival signaling in response to acquired gefitinib resistance in gefitinib-sensitive and wtEGFR-expressing cancer cells (16,17). In addition, it has also been reported that a non-smoking female NSCLC patient with wtEGFR expression developed acquired gefitinib resistance without any identifiable EGFR mutations (18).…”
mentioning
confidence: 99%
“…The PPI landscape of p85 (PI3K) was investigated as the first phase in identifying drivers of cell proliferation in MM cells. H929 cells were lysed, and a polyclonal antibody recognizing the p85 regulatory subunit of PI3K was used to immunoprecipitate its associated proteins according to previously published studies (5,33,34). Immunoprecipitated p85 protein complexes were eluted and run by mini SDS/PAGE ∼1/6 of the gel distance and stopped.…”
Section: Analysis Of Activating Signaling Pathways Using a Multifacetedmentioning
confidence: 99%